The Influence Of Financial Inclusion, Consumptive Lifestyle And Promotion On The Level Of Impulse Shopping In Management Students Of Universitas Pembangunan Panca Budi Medan - Manullang, Ica Delina; Hernawaty, Hernawaty (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This research aims to test and determine the influence of financial inclusion, consumer lifestyle and promotion on impulsive shopping among students at the Pancabudi Development University, Medan. The method used is a quantitative approach with the help of the SPSS application. This research uses multiple linear regression analysis. The sample in this study was 82 respondents. Primary data collection uses a questionnaire. And the results of this research show that financial inclusion, consumer lifestyle and promotion simultaneously have a positive and significant effect on impulsive shopping among students at the Pancabudi Development University, Medan